Unpacking The Role of Poverty and Cultural Norms in The Marginalization of Girls' Education in Adamawa State, Nigeria - Asaju, Kayode; Kamale, Markus Yohanna (ILIN Education Indonesia, 2025)
This study examined the impact of poverty on the education of the girl-child in Adamawa State, Nigeria. The primary objective is to examine the effect of poverty on girl-child education in Adamawa State, the efforts put in place at reducing poverty and enhancing the girl-child education, effective are these efforts in enhancing girl- child education in the challenges militating against the efforts put in place at curbing poverty against the girl-child education in the state. The research employs a qualitative approach, utilizing secondary data analyzed through content analysis and framed within the cultural feminist theoretical perspective. Findings reveal that poverty exacerbates gender disparities in education, as girls from low-income families are more vulnerable to early marriage, domestic labor, and withdrawal from school due to financial constraints. Additionally, cultural attitudes that undervalue female education and rising education costs further limit opportunities for girls. The study concludes that comprehensive and gender-sensitive interventions such as scholarship programs, community sensitization, and enhanced educational infrastructure are essential to promoting equitable access to education and breaking the cycle of poverty for the girl-child in Adamawa State.